How Has A Small UK Music Company Utilised Networks In Order To Maintain Niche Market Leadership in A Market Dominated by Larger Firms? - Miranda, Kempin (2010)
This study utilises a qualitative study framework in order to assess the importance of networks for the continued niche market leadership of a small music company operating in the UK. Specifically, this study concentrates on the relevance of social and external networks. The study focuses on Eagle Rock Entertainment Ltd (hereafter, ‘Eagle’), a company specialising in audio-visual music programming. In order to assess the impact of networks on the company, interviews were undertaken with five internal employees of Eagle and with two external industry experts. Questions related to ways in which Eagle avoided direct competition with larger firms and to what extent networks are pivotal for their sustained niche market leadership. The findings illustrate the paramount importance of social networks in particular as they facilitate access to market opportunities, international distribution systems and assist in the formation of external networks. Eagle’s resource liabilities stem from their lack of signed artists which are able to be exploited within their audio-visual programming. As such, external networks allow Eagle to access a wider variety of material and therefore, enable them to overcome disadvantages associated with size. Furthermore, without external networks Eagle would not be able to distribute their product on such a global scale. The use of networks, in particular social networks, has spread Eagle’s reputation for excellence in the audio-visual sector. As such, the major music companies have been more prepared to license out material to Eagle rather than enter the sector more aggressively. Consequently, it is suggested that not only do networks provide benefits in terms of increasing Eagle’s internal capabilities but they allow the company to continue to operate in a market separate from their larger rivals.